Recent advances about metal–organic frameworks in the removal of pollutants from wastewater - Gao, Qiang; Xu, Jian; Bu, Xian-He (Coordination chemistry reviews, 2019)
•The meaning and significance of the removal of pollutants from wastewater are illustrated.•Representative studies about MOFs for the removal of contaminants from wastewater are illustrated.•Perspectives and challenges about the removal of pollutions from wastewater by MOFs are presented. Water pollution is one of the most serious worldwide problems that endangers the survival and development of human society. Therefore, the effective and efficient removal of contaminants from water has become a hot topic. As a fast-growing branch of coordination chemistry, metal–organic frameworks (MOFs) with tailorable porous structures and numerous active sites have proved to be ideal adsorbents or photocatalysts for water purification. In this review, recent advances in the removal and degradation of water pollutants by MOFs are highlighted. In addition, the challenges and prospects in this active field are also briefly discussed.